Analysis of the Concept of Friction Force, Centripetal Force, and Maximum Speed on The Piket Nol Lumajang's Route as a Physics E-Module Design - Firda Shahira; Albertus Djoko Lesmono; Rif'ati Dina Handayani (Scientiae Educatia: Jurnal Pendidikan Sains)
The cause of students' difficulties in understanding physics material is that students cannot relate formal knowledge to everyday life, and there is a lack of contextual teaching materials. One way to overcome these problems is to examine examples of events in students' lives to serve as a reference for designing teaching materials. The Lumajang' Piket Nol line has extreme track characteristics, and accidents often occur. This analysis aims to examine the friction force, centripetal force, and maximum speed on the Piket Nol Line. The results of the analysis are used as a reference for designing physics teaching materials in the form of e-modules. The method used in this research is content analysis. The object of this research is four trajectories chosen by the researcher because of an accident. The four tracks include a straight track, a straight incline/decline, a flat bend, and an uphill/downhill bend. This analysis shows that the amount of friction force, centripetal force, and maximum speed increases when the initial speed is greater. The analysis results were used as a reference for the design of contextual e-modules in the form of flipbooks.